Sistem Monitoring PV Menggunakan Simulasi Proteus Untuk Pembelajaran Mahasiswa Teknik Elektro UNsP - Marina Artiyasa; Isdaryanto Iskandar; Harurikson Lumbantobing (Universitas Nusa Putra, 2022)
Photo Voltaic system is now being promoted, mainly because fossil energy will run out, therefore we use Photovoltaic a lot, but monitoring has not been widely used, especially remotely, so on this occasion we will use Proteus simulation to monitor so that the situation of our PLTS remains under control. The components used are arduino uno as a microcontroller, then LCd to display values, then solar cell, battery, breadboard, esp8266 module for wifi, current sensor and voltage sensor for monitoring current and voltage. The results of the above design use Proteus simulation and use Arduino software for programming, and can run well by displaying monitoring results on the LCD and also in the Arduino program, this is done before being applied to designs that use actual tools.this simulation is good so the student can study in the computer lab ., it prove with the grade before treatment and after treatment from 66, 3 become 79